The Effect of Exercise on Sleep Quality in the Elderly Undergoing Hemodialysis - Mansour Ali-Mohammadi; Ali Samadi; Maryam Jadid-Milani (Iran University of Medical Sciences, 2021)
Background & Aims The elderly population in the world as well as in Iran is growing, which may lead to a significant increase in chronic diseases, especially kidney failure and its related complications such as sleep disorders; this can result in disturbance of daily activities and poor quality of life. Therefore, the present study aimed to determine the effect of exercise during dialysis on sleep quality in the elderly people undergoing hemodialysis. Materials & Methods This is an experimental study that was performed on 30 elderly people undergoing hemodialysis (15 in the experimental group and 15 in the control group) in Ghiasi Charity Center in Tehran in 2010-2011. Demographic information form, cognitive abilities screening instrument-short form and Pittsburg sleep quality index were used for data collection. In the experimental group, aerobic and resistance exercise was performed for 8 weeks and 3 times a week during dialysis. In the control group, routine care was performed and no additional intervention was implemented. Results In comparison with pre-test (before the first week), at post-test (after the eighth week) the quality of sleep improved significantly in the experimental group (P<0.0001), but in the control group the sleep quality scores decreased significantly (P=0.001), which suggests the quality of sleep was worsened. Between group comparisons revealed that at baseline there was a significant difference between groups and the control group had better sleep quality (P=0.035), but in the post-test sleep quality was significantly in the experimental group (P<0.0001). Conclusion As exercise had a positive effect on sleep quality in elderly people under hemodialysis, it seems that it may be used as a safe low-cost and effective treatment for improving the sleep quality in this population.